Influence of variation in construction parameters on the stability of the surrounding rock in soft rock tunnels - Li, Junhong; Hong, Shaopan; Xiong, Yu; Chen, Yuxue; Nie, Qiqiang (Frontiers in Earth Science, 2024)
The stability of the surrounding rock is an important engineering challenge for soft rock tunnels. Based on the FLAC3D finite difference numerical simulation software, this paper analyzes the typical area of the Fenghuang Mountain tunnel in the Chuxiong section of the Central Yunnan Water Diversion Project. Three construction methods are implemented: three-bench method, reserved core soil method, and CD method, with two excavation parameters being different lengths of the upper step and heights of the lower step. The whole excavation process of the red layer soft rock tunnel is simulated under four supporting conditions: different bolt lengths, different bolt spacings, different initial support thicknesses, and varying advanced grouting strengths. The results indicate that the CD method has a strong constraint on the vertical displacement of the surrounding rock at the arch, while the reserved core soil method has a better effect on controlling the uplift value, and the three-step method has a better constraint on the horizontal convergence of the surrounding rock at the arch waist. The increase in the distance between the upper and lower steps has a great influence on the horizontal convergence value of the tunnel, and the lower steps have a better inhibition effect on the horizontal convergence value of the surrounding rock at the tunnel arch. The increase in the lining thickness has a significant effect on restraining the deformation of the surrounding rock, and advanced grouting is efficient in enhancing the mechanical parameters of the surrounding rock and reducing the displacement of the surrounding rock. The support optimization engineering application is carried out in the 6# construction branch tunnel of the Fenghuang Mountain tunnel, yielding good results.